Pangenome analysis of the genus Herbiconiux and proposal of four new species associated with Chinese medicinal plants - Deng, Yang; Jiang, Zhu-Ming; Han, Xue-Fei; Su, Jing; Yu, Li-Yan; Liu, Wei-Hong; Zhang, Yu-Qin (Frontiers in Microbiology, 2023)
Five Gram-stain-positive, aerobic, non-motile actinobacterial strains designated as CPCC 205763T, CPCC 203386T, CPCC 205716T, CPCC 203406T and CPCC 203407 were obtained from different ecosystems associated with four kinds of Chinese traditional medicinal plants. The 16S rRNA gene sequences of these five strains showed closely related to members of the genus Herbiconiux of the family Microbacteriaceae, with the highest similarities of 97.4–99.7 % to the four validly named species of Herbiconiux. In the phylogenetic trees based on 16S rRNA gene sequences and the core genome, these isolates clustered into the clade of the genus Herbiconiux within the lineage of the family Microbacteriaceae. The overall genome relatedness indexes (values of ANI and dDDH) and the phenotypic properties (morphological, physiological and chemotaxonomic characteristics) of these isolates, readily supported to affiliate them to the genus Herbiconiux, representing four novel species, with the isolates CPCC 203406T and CPCC 203407 being classified in a same species. For which the names Herbiconiux aconitum sp. nov. (type strain CPCC 205763T = I19A-01430T = CGMCC 1.60067T), Herbiconiux daphne sp. nov. (type strain CPCC 203386T = I10A-01569T = DSM 24546T = KCTC 19839T), Herbiconiux gentiana sp. nov. (type strain CPCC 205716T = I21A-01427T = CGMCC 1.60064T), and Herbiconiux oxytropis sp. nov. (type strain CPCC 203406T = I10A-02268T = DSM 24549T = KCTC 19840T) were proposed, respectively. In the genomes of these five strains, the putative encoding genes for amidase, endoglucanase, phosphatase and superoxidative dismutase were retrieved, which were classified as biosynthetic genes/gene-clusters regarding plant growth-promotion (PGP) functions. The positive results from IAA-producing, cellulose-degrading and anti-oxidation experiments further approved their potential PGP bio-functions. Pangenome analysis of the genus Herbiconiux supported the polyphasic taxonomy results and confirmed their bio-function potential.